2023
DOI: 10.21203/rs.3.rs-2495276/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three-Dimensional Evaluation of Skeletal Stability after Surgery-First Bimaxillary Surgery for Class III Asymmetry in 70 Consecutive Patients

Abstract: Background This study (1) evaluated the stability of the maxillary and mandibular proximal and distal segments after surgery-first bimaxillary surgery for class III asymmetry and (2) determined whether the stability of a given mandibular segment was related to the movement of any segment during surgery or postsurgical stability of any other segment. Methods Seventy adults with class III asymmetry consecutively corrected through surgery-first Le Fort I osteotomy and bilateral sagittal split osteotomy were inv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Park et al found a reduction in oropharyngeal volume in Class III orthognathic surgery patients from preoperative to 4.6 months postoperatively, followed by an increase from 4.6 months postoperatively to 1.4 years postoperatively, indicating a tendency for upper airway morphology to relapse postoperatively [13]. The rotational setback of the jaw in the deviation group may result in greater tension in the soft tissues on the upper airway and tongue than in the nondeviation group, leading to a more pronounced trend of relapse [14]. Additionally, the postoperative conebeam computed tomography (CBCT) scans selected for this study were taken one year postoperatively, and differences in relapse severity may have led to a narrowed gap in upper airway changes between the two groups.…”
Section: Discussionmentioning
confidence: 98%
“…Park et al found a reduction in oropharyngeal volume in Class III orthognathic surgery patients from preoperative to 4.6 months postoperatively, followed by an increase from 4.6 months postoperatively to 1.4 years postoperatively, indicating a tendency for upper airway morphology to relapse postoperatively [13]. The rotational setback of the jaw in the deviation group may result in greater tension in the soft tissues on the upper airway and tongue than in the nondeviation group, leading to a more pronounced trend of relapse [14]. Additionally, the postoperative conebeam computed tomography (CBCT) scans selected for this study were taken one year postoperatively, and differences in relapse severity may have led to a narrowed gap in upper airway changes between the two groups.…”
Section: Discussionmentioning
confidence: 98%